Psychopathological features of anxiety disorders in patients with cardiac arrhythmias before and after cardiac pacemaker implantation - B. G. Iskenderov; E. V. Petrova; M. V. Docheva (Российский кардиологический журнал)
In 108 patients, clinico-psychopathological features of anxiety disorders were studied before and after cardiac pacemaker (CPM) implantation, using the Hospital Anxiety and Depression Scale (HADS). Both at baseline and after CPM implantation, anxiety-phobic and general anxiety disorder were the most common features. In patients with CPM, prevalence and severity of anxiety disorders correlated with electrocaridostimulation (ECS) regime and duration, cardiac arrhythmia severity and ECS complications. These factors point to the need for psychological rehabilitation in CPM individuals